CONSTRUCTION OF THE ADDED WHOLE CURVE WITH BEFOREHAND BY THE SET GREAT NUMBER OF IMPERFECT VECTORS - Савчук, Ярослав Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
For the beforehand set great number of vectors of certain structure the entire curve of complete positive order, for which the structure of derfect vectors of the proper added whole curve coincides with this great number, is built.